Nrf-2/HO-1 modulatory effects on Ocimum gratissimum flavonoid-rich leaf extract in the livers of streptozotocin-induced diabetic rats - Ajiboye, Basiru Olaitan; Salami, Salmat Adenike; Okesola, Mary Abiola; Patrick, Divine pope; Omojemite, Taiwo Oluwapelumi; Omolare, Blessing Oluwasayo; Ajuwon, Olawale Razaq; Alsanie, Walaa F.; Alamri, Abdulhakeem S.; Alhomrani, Majid; Alshammary, Amal F.; Asdaq; et al. (Springer Nature, 2026)
The present study examined the modulatory effects of Ocimum gratissimum leaf flavonoid-rich extracts on the Nrf-2 and HO-1 pathways in the livers of streptozotocin-induced diabetic rats. The animals were divided into five groups (n = 8). These included a normal control, a diabetic control, diabetic rats administered low (LDOGFL) or high (HDOGFL) doses of Ocimum gratissimum leaf flavonoid-rich extracts at 150 and 300 mg/kg, respectively, and diabetic rats administered 200 mg/kg metformin. The animals were sacrificed on the 22nd day of the study, the liver was excised, and different biochemical parameters were evaluated. At the end of this study, diabetic rats administered LDOGFL and HDOGFL presented significant (p < 0.05) decreases in fragmented DNA, protein carbonyl and lipid peroxidation levels, as well as glucose-6-phosphatase, and fructose 1,6 bisphosphatase activities. However, there was a significant (p < 0.05) increase in the levels of antioxidant biomarkers; phosphatase and transaminase activities; GLUT 2 and glycogen levels; glycogen synthase and phosphorylase; hexokinase, pyruvate kinase and glucose-6-phosphate dehydrogenase activities; and serum albumin and insulin in diabetic rats treated with extracts. Furthermore, there was a substantial increase in the relative gene expression of Nrf2 and HO-1, especially in diabetic rats administered LDOGFL. Hence, these findings suggest that these extracts might be helpful in managing hepatopathy in patients with diabetes mellitus.